SOSIALISASI MENJAGA KESEHATAN MATA UNTUK MENINGKATKAN PENGETAHUAN TENTANG KATARAK PADA LANSIA DI SARANGAN - Garry Ivan Yurangga; Wahyu Budiana; Murni Marlina Simarmata (Jurnal Mata Optik, 2022)
The study aims to find out how well people understand cataract disease, while also inducing people to better protect their eyes from exposure to sunlight. This research uses qualitative methods with a literature descriptive  approach with observation and interview techniques. The subject of the study is a citizen active on the coast of the lagoon at the age of 50 years and more.  The results show that the residents of the nest tend not to know cataracts that care less about or care for eye health. The socialization absence of local health services is one factor that makes people less aware of cataracts, less concerned about their eye health